DEATH AND ONE OF ITS MANY NARRATIVES: THE STORY OF THE STOLPERSTEINE-PROJECT IN GERMANY - Suganda, Sonya Puspasari (UI Scholars Hub, 2020)
Within the contemporary German society, there is an initiative that has been ongoing for over 25 years. This initiative is called the Stolperschwelle which is conducted to commemorate the falling victims of the Nazi. An artist named Gunter Demnig started the whole project in 1992, and in 2017 – with the support of the society – he succeeded to place the 70.000th stumbling stone (in German; Stolpersteine), a 96 mm x 96 mm x 100mm brass plaques in the pavement of the last victim’s address. At first, it was meant to remember the death of the Jewish during the Nazi era, but nowadays the stumbling stones also represent the death of the marginalized groups including the Gipsy, the homosexuals, people with physical disability, and people who are falsely accused because of their religious and political belief. In the Stolpersteine-project, anybody can show their respect for the victims of the Nazi by sponsoring a stumbling stone – its manufacture and its installation for 120 euro – dedicated to one victim. This article analyses how this Stolpersteine-project can be viewed from various perspectives by using socio-cultural, historical, and urban landscape perspectives. The study is conducted using a qualitative approach through literature review. The findings show that the main story evolving around the Stolperstein project is the death of someone, caused by extremely terrible matter. By engaging in the Stolperstein, the modern German society tries to commemorate someone’s death, even someone they do not personally know. The historical perspective looks at the difference of microhistory and macrohistory when it comes to one nation’s history. In the Stolpersteine project, people deal greatly with microhistory. Finally, the urban landscape perspective emphasizes that the construction of space can contribute to reliving the past as well as building a better understanding for a nation’s generation.